Riding the bubble or taken for a ride? Investors in the British bicycle mania - William Quinn; John D. Turner (Queen's University Centre for Economic History (QUCEH), 2021)
Clientele-based theories explaining asset price bubbles are often difficult to test because the identities of investors cannot easily be tracked over time. This paper tests these theories using a hand-collected sample of 12,000 investors during an asset price reversal in the shares of British bicycle companies between 1895 and 1900. We find that informed investors reduced their holdings substantially during the crash, suggesting that they were riding the bubble. Those who performed worst were not typically the least informed groups, but gentlemen living near a stock exchange, who had the most time, money, and opportunity to engage in speculation.
Keywords: G01; N23; 330; British financial history; financial bubbles